2012
DOI: 10.1016/j.taap.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor nuclear translocator in human liver is regulated by miR-24

Abstract: Aryl hydrocarbon receptor nuclear translocator (ARNT) forms a heterodimer with aryl hydrocarbon receptor or hypoxia inducible factor 1α to mediate biological responses to xenobiotic exposure and hypoxia. Although the regulation mechanism of the ARNT expression is largely unknown, earlier studies reported that the human ARNT protein level was decreased by hydrogen peroxide or reactive oxygen species. These stimuli increase the miR-24 level in various human cell lines. In silico analysis predicts that some micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
0
22
1
Order By: Relevance
“…et al, 2012), and miR-27b is known to regulate CYP1B1 (Tsuchiya et al, 2006). MicroR-24 indirectly regulates CYP1A1 through its effects on the Aryl hydrocarbon receptor nuclear translocator (ARNT) (Oda et al, 2012) and HNF4A (Takagi et al, 2010). However, none of these were regulated by rifampin in our studies.…”
Section: Discussioncontrasting
confidence: 59%
“…et al, 2012), and miR-27b is known to regulate CYP1B1 (Tsuchiya et al, 2006). MicroR-24 indirectly regulates CYP1A1 through its effects on the Aryl hydrocarbon receptor nuclear translocator (ARNT) (Oda et al, 2012) and HNF4A (Takagi et al, 2010). However, none of these were regulated by rifampin in our studies.…”
Section: Discussioncontrasting
confidence: 59%
“…The cDNA was synthesized from total RNA prepared from cells or human liver samples. The primers for human CYP2A6 (Nakajima et al, 2006b), human b-actin (Oda et al, 2012), and GAPDH (Tsuchiya et al, 2004) were described previously. A 1-mL portion of the reverse-transcribed mixture was added to a PCR mixture containing 10 pmol each primer, 12.5 mL SYBR Premix Ex Taq solution, and 75 nM ROX in a final volume of 25 mL.…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed that AHR was modulated by miR-124 in neuroblastoma SK-N-SH cells . In addition, miR-24 was shown to regulate the AHR dimer partner, aryl hydrocarbon receptor nuclear translocator, and thus interfere with expression and induction of CYP1A1 in Huh-7 and HepG2 cells (Oda et al, 2012).…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 99%